Musical Ekphrasis in I.S.Turgenev’s Novel Rudin - Troitsky, Nóra (Slavica, 2021)
Turgenev-scholars often use the word "musicality" or "musical code" in the analysis of the writer’s fictional prose, since Turgenev often refers to music in dialogues, in descriptions of the characteristics of the heroes. This article focuses on a musical piece, which occurs in the third chapter in Turgenev’s Rudin,F. Schubert’s famous “Erlkönig” Lied. This musical scene of the short novel evokes the mysterious atmosphere of Goethe’s ballad. Schubert’s “Erlkönig” thematizes some of the parallel motifs that appear in the novel such as travel, the motive of finding a path, and the problem of intransmissibility. My aim is to examine how these motifs are manifested in Turgenev’s novel. On the one hand, this research examines the purpose of the musical ekphrasis and how it might foreshadow his fate. This mimetic musical ekphrasis allows us to interpret the novel from different aspects. On the other hand, this intertextual element can be perceived as “mise en abyme” (L. Dällenbach), proceeding from the fact that the function of a diminutive mirror provides a key to a deeper understanding of the text.